The Use of Ulster Speech by Michael Longley and Tom Paulin - Kruczkowska, Joanna (Text Matters: A Journal of Literature, Theory and Culture, 2011)
The article examines the application and exploration of Ulster dialects in the work of two poets of Northern Irish Protestant background, Tom Paulin and Michael Longley. It depicts Paulin's attitude to the past and the present of their community of origin, the former positive and the latter negative, which is responsible for the ambiguities in his use of and his comments on the local speech. Both poets employ the vernacular to refer to their immediate context, i.e. the conflict in Ulster, and in this respect linguistic difference comes to be associated with violence. Yet another vital element of their exploration of the dialect is its link to their origins, home and the intimacy it evokes, which offers a contrary perspective on the issue of languages and makes their approach equivocal. This context in Paulin's poetry is further enriched with allusions to or open discussion of the United Irishmen ideal and the international Protestant experience, and with his reworking of ancient Greek myth and tragedy, while in Longley's poetry it is set in the framework of "translations" from Homer which, strangely enough, transport the reader to contemporary Ireland. While Longley in his comments (interviews and autobiographical writings) relates the dialect to his personal experience, Paulin (in his essays and in interviews) seems to situate it in a vaster network of social and political concepts that he has developed in connection with language, which in Ireland has never seemed a neutral phenomenon detached from historical and political implications. Longley's use of local speech is seldom discussed by critics; Paulin's, on the contrary, has stirred diverse reactions and controversies. The article investigates some of these critical views chiefly concerned with the alleged artificiality of his use of local words and with his politicizing the dialects. Performing the analysis of his poems and essays, the article argues for Paulin's "consistency in inconsistency," i.e. the fact that his application of dialectal words reflects his love-hate attitude to his community of origin, and that in the clash of two realities, of the conflict and of home, his stance and literary practice is not far from Longley's, which has been regarded as quite neutral as one can infer from the lack of critical controversy about it. The voices of the two poets and their use of local speech provide a crucial insight into the Northern Irish reality with all its intricacy and paradox.